2006
DOI: 10.3892/ijo.28.6.1345
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of esophageal squamous cell carcinoma patients treated with definitive chemoradiotherapy: Clinical implications

Abstract: Abstract. In esophageal squamous cell carcinoma (ESCC), chemoradiotherapy (CRT) has a curative potential even in cases of locally advanced carcinoma. However, only about half of the patients benefit from CRT, and an accurate prediction of sensitivity to CRT is eagerly awaited. Using microarrays, we analyzed gene-expression patterns of pretreatment biopsy specimens from 33 patients with CRT alone including longterm survivors, more than 3 years (14 cases) and short-term survivors, less than 1 year (11 cases). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 13 publications
0
30
1
1
Order By: Relevance
“…[39][40][41] The effect of chemoradiotherapy in esophageal cancer is correlated with the number of CD8 1 T cells in the tumor of each patient, and the patterns of gene expressions for T cell activation and for tumor vessel formation may become good markers for identifying potential long-term survivors. 11 However, in the present study, no correlations between numbers of macrophages, CD8 1 T cells, or mast cells and response to first-line chemotherapy were found ( Table 2). The results of our study suggested that patients with a favorable or unfavorable prognosis could be identified by the status of tumor-infiltrating macrophages and CD8 1 T cells in tumor biopsy specimens before receiving chemotherapy regardless of chemotherapy response.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…[39][40][41] The effect of chemoradiotherapy in esophageal cancer is correlated with the number of CD8 1 T cells in the tumor of each patient, and the patterns of gene expressions for T cell activation and for tumor vessel formation may become good markers for identifying potential long-term survivors. 11 However, in the present study, no correlations between numbers of macrophages, CD8 1 T cells, or mast cells and response to first-line chemotherapy were found ( Table 2). The results of our study suggested that patients with a favorable or unfavorable prognosis could be identified by the status of tumor-infiltrating macrophages and CD8 1 T cells in tumor biopsy specimens before receiving chemotherapy regardless of chemotherapy response.…”
Section: Discussioncontrasting
confidence: 70%
“…29 The presence of tumor-infiltrating CD8 1 T cells has previously been reported to be associated with a favorable outcome, the same as in our own study. [5][6][7][8][9][10][11][12]30 Patients in the HNM and HNT group had significantly better survival (median survival was 495 days; 1-year survival rate was 68.5%) than patients in the HNM group (median survival, 440 days; 1-year survival rate, 60.8%; Fig. 2C) and patients in the HNT group (median survival, 388 days; 1-year survival rate, 53.4%; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite rapid advancement of multimodal treatments for patients afflicted with ESCC, the prognosis has not been significantly improved, with an average 5 years survival rate of 10-20% (2,5,6). The prediction of ESCC clinical prognosis still depends on conventional pathologic variables such as tumor size, tumor grade, lymph node and distal metastasis status (7)(8)(9). Therefore, it is of great clinical value to find sensitive and specific early biomarkers for the diagnosis and prognosis of this malignancy, as well as novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%